1999
DOI: 10.1093/emboj/18.22.6299
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic forces drive spontaneous membrane insertion of the bacteriophage Pf3 coat protein without topological control

Abstract: Bacterial integral inner membrane proteins are either translocated across the lipid bilayer using an energydriven enzyme, such as the Sec translocase, or they might interact directly with the membrane due to hydrophobic forces. We report that the single-spanning Pf3 coat protein is spontaneously inserted into the membrane of Escherichia coli and requires the electrical component of the membrane potential (∆Ψ) to translocate its N-terminal region. This results in a final N out C in orientation of the protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 33 publications
8
98
0
1
Order By: Relevance
“…The Proton Motive Force Is Required for Membrane Insertion of FtsQ-The PMF has been shown to play an important role in the insertion of some IMPs (27) and membrane topology control (28,29). The ATP needed for the translation reaction is also used by the F 1 F 0 ATPase to generate a PMF.…”
Section: Co-translational Insertion Of Ftsq Intomentioning
confidence: 99%
“…The Proton Motive Force Is Required for Membrane Insertion of FtsQ-The PMF has been shown to play an important role in the insertion of some IMPs (27) and membrane topology control (28,29). The ATP needed for the translation reaction is also used by the F 1 F 0 ATPase to generate a PMF.…”
Section: Co-translational Insertion Of Ftsq Intomentioning
confidence: 99%
“…Hydrophobicity of the TMD-Because hydrophobic forces have a crucial role in membrane translocation of the E. coli Secindependent pathway (17,18,24,26), we examined the role of hydrophobic forces on the insertion of T7-Su8 across INVs. We constructed the T7-Su8 mutants TM1 and TM2, in which hydrophobic residues in the former (TM1) and the latter (TM2) half of the TMD were replaced by hydrophilic residues (Fig.…”
Section: Insertion Of T7-su8 Across the Membrane Depends On Thementioning
confidence: 99%
“…The M13 procoat protein is synthesized with a cleavable signal peptide and spans the membrane once with the processed N terminus exposed to the periplasm and the C terminus remaining in the cytoplasm (18 -24). The Pf3 coat protein is synthesized without a cleavable signal sequence and inserts into the membrane once, exposing the N-terminal segment to the periplasm and the C-terminal segment to the cytoplasm (25,26). In contrast to the predicted direct insertion mechanism, Samuelson et al (27) demonstrated that insertion of the M13 procoat protein across the membrane depends on a Oxa1p homologue, YidC.…”
mentioning
confidence: 99%
“…When liposomes containing DAG were used for M13 procoat and Pf3 coat integration, DAG also blocked the spontaneous integration of these proteins completely (7,17). 3L-Pf3 coat is a mutant version of Pf3 coat in which three leucine residues are inserted in the middle of the TM domain (18). Although integration of M13 procoat and Pf3 coat proteins is stimulated by the membrane potential, 3L-Pf3 coat does not require the membrane potential (18).…”
Section: Yidcmentioning
confidence: 99%
“…3L-Pf3 coat is a mutant version of Pf3 coat in which three leucine residues are inserted in the middle of the TM domain (18). Although integration of M13 procoat and Pf3 coat proteins is stimulated by the membrane potential, 3L-Pf3 coat does not require the membrane potential (18). In this sense, insertion of this protein is the most spontaneous.…”
Section: Yidcmentioning
confidence: 99%